Gushen Antai pill for expected normal ovarian responders undergoing IVF-ET (GSATP-FreET): interim analysis of a randomized controlled trial - Ying Xu; Xin Hu; Kai-Liang Ai; Zhen-Gao Sun; Jing-Yan Song (Contraception and Reproductive Medicine)
Abstract Introduction Optimal luteal phase support (LPS) is essential for successful embryo transfer. In our previous study, we found that LPS combined with Gushen Antai pill (GSATP) could significantly improve ongoing pregnancy rate (OPR) and reduce threatened abortion rate after frozen-thawed embryo transfer (FET). Despite this, no high-quality studies have been performed on the combination of LPS and GSATP for the embryo transfer of fresh IVF cycles. Methods A randomized, double-blind, placebo-controlled trial started on June 15, 2021 at 20 reproductive centers of public tertiary hospitals. In total, 371 eligible women with expected normal ovarian reserve (NOR) were age-stratified and randomly assigned to either the GSATP group or the placebo group at random in an equal ratio. The primary outcome is OPR. The report presents data from an interim analysis used for regulatory submissions. Results In the per-protocol cohort, the OPR in the GSATP group and placebo group were 40.3% and 38.4%, respectively. Nevertheless, the GSATP group showed a significantly lower incidence of vaginal bleeding (11.3% vs. 21.6%, p = 0.046), threatened miscarriage (16.0% vs. 29.4%, p = 0.021), and functional constipation (16.0% vs. 29.4%, p = 0.021) than the placebo group during the first trimester of pregnancy. Discussion In the interim analysis, while GSATP did not result in better pregnancy outcomes for NOR patients undergoing fresh embryo transfers, it did improve common symptoms observed during the early pregnancy phase, such as vaginal bleeding, threatened miscarriage, and functional constipation. Trial registration National Institutes of Health clinical trials database, NCT04872660. Registered 4 May 2021, https//clinicaltrials.gov/study/NCT04872660.